Controlling the properties of layered self-organized Ge clusters in silica matrix - Pinto, S. R. C. (2012)
Si and Ge nanocrystals (NCs) embedded in a dielectric matrix, such as SiO2, have attracted great interest for many relevant technological applications. There are many studies about Ge NCs embedded in single layer of SiO2 [1]. However, there are only a few published results about Ge NCs embedded in SiO2 multilayer [2]. Using a multilayered superlattice approach one can achieve a higher density and more uniform size and spatial distributions of NCs, which is very important for the collective behavior effects. In this work we investigate the structural properties of Ge quantum dot (QD) lattices formed in amorphous silica matrix by magnetron sputtering deposition of (Ge+SiO2)/SiO2 multilayer. We demonstrate the dependencies of QD shape, size, separation and spatial arrangement type on Ge-rich (Ge+SiO2) layer thickness. We show that the formed QDs are elongated in direction perpendicular to the multilayer surface (vertical direction). The vertical size of the QDs and their separation in the vertical direction can be tuned by changing the Ge-rich layer thickness. The mean values of the QDs lateral size of their lateral separation are not affected by the thickness of the Ge-rich layer. However, the thickness of Ge-rich layer significantly affects the regularity in QD ordering. In addition, we investigate the dependence of the multilayer atomic composition and QD inner crystalline structure on the deposition parameters, which are important for future device applications. [1] S. Takeoka, K. Toshikio, M. Fujii, S. Hayashi, and K. Yamamoto, Phys. Rev. B 61, 15988 (2000) [2] F. Gao, M. A. Green, G. Conibeer, E. C. Cho, Y. D. Yang, I. Pere-Wurfl, and C. Flynn, Nanotechnology 19, 455611 (2008)